The Comparison with Commercial Antioxidants, Effects on Colour, and Sensory Properties of Green Tea Powder in Butter - Songül Çakmakçı; İlhami Gülçin; Engin Gündoğdu; Hatice Ertem Öztekin; Parham Taslimi (MDPI AG, 2023)
Oxidation is one of the most important factors limiting shelf life and is a major deterioration process affecting both the sensory and nutritional quality of food. The high oxidation stability of lipids, which can be improved by the addition of antioxidants, is important for health protection, food quality, and economic reasons. In recent years, research on plant-derived antioxidants for use in human health and food has steadily increased. The aim of this study was to compare the antioxidant effects of green tea powder (GTP) in butter with those of commercial antioxidants (BHA, BHT, α-tocopherol, and Trolox). In addition, the effects on colour, sensory, gross physicochemical properties, and β-carotene content were investigated in butter. After the separation of butter into five pieces, the first part was chosen as the control sample without GTP; the second part has 100 mg/kg of BHT added to it; and the third, fourth, and fifth parts had 1, 2, and 3% of GTP added in the samples. They were stored at 4 ± 1 °C. Analysis was performed at intervals of 15 days. According to the iron reduction, CUPRAC and FRAP methods were performed, and parallel results were observed. Using the radical elimination methods (ABTS, DPPH•, and DMPD•+), IC50 values were calculated for the samples. According to the IC50 values, the GTP-containing samples were good antioxidants. The total phenolic andf β-carotene contents increased as the GTP addition increased. The addition of GTP had an antioxidant capacity equal to or higher than that of the BHT-added sample. For the production of a sensory-pleasing, greenish-coloured, new functional butter, the 1% GTP addition showed the most positive results.